Role of microstructure and crystallographic orientation in fatigue crack failure analysis of a heavy haul railway rail. (February 2019) - Masoumi, Mohammad; Sinatora, Amilton; Goldenstein, Hélio
Abstract: Failure analysis studies were carried out on a used rail with head check defects to characterise the effect of microstructural features (i.e. microstructure and crystallographic orientation) on fatigue crack nucleation and propagation. The morphological differences of the pearlitic structure were analysed using secondary electron microscopy and electron backscattered diffraction techniques from non-deformed to deformed areas, as a function of depth distance. Cementite thinning, bending and fragmenting were characterised in a few microns (≈20 μm) below the rail surface, caused by induced shear strain. The rail surface showed a significant hardness increment (~50%) rather than the initial state of the pearlite morphology. Ferrite peak broadening and the presence of nanocrystalline carbon supersaturated ferrite were observed by X-ray diffraction, attributed to the accumulation of dislocation density in ferrite lamellae and ferrite/cementite interfaces during cyclic train passing. Electron backscattered diffraction analysis of both cracked and crack-resistance areas revealed that the high-distorted Taylor factor grains accompanied by grains oriented {001} parallel to the train running direction were responsible for fatigue crack formation and propagation. Highlights: Studying the crystallographic texture evolution under due to severely cyclic plastic deformation by train passing. Characterizing the nanocrystalline carbon supersaturated ferrite using X-ray diffraction. Analysing the dislocation density changes from the axis perpendicular to the crack growth direction using EBSD.